2020
DOI: 10.1002/cbdv.201900674
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Limonoids Isolated from the Fruits of Melia toosendan and Their Antifeedant Activity against Pieris rapae

Abstract: We thank Prof. Dr. Jia-Mei Li in Henan Agricultural University for the identification of the plant material.The fruits of Melia toosendan SIEB. et ZUCC. (Meliaceae) are a source of bioactive limonoids that can be used as effective pesticides. In this study, two novel limonoids, 6-acetylsendanal and 6-ketocinamodiol, were isolated together with fourteen known compounds, namely four protolimonoids, six trichilin-class limonoids, and four Cseco limonoids. The structures of the new compounds were determined by ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…Peak at 19.7 min with [M+H] + at m/z 613 was tentatively assigned to of salannal [17] . The main observed fragments were ions at m/z 553 (−60) corresponding to the loss of C 2 H 4 O 2 ascribable to neutral loss of acetic acid (substituent in C‐3) or methoxy formate moiety (chain in position C‐11); m/z 513 (−100) tiglic acid C 5 H 8 O 2 (C‐1), m/z 581 (−32) corresponding to the loss of formaldehyde (substituent at C‐4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Peak at 19.7 min with [M+H] + at m/z 613 was tentatively assigned to of salannal [17] . The main observed fragments were ions at m/z 553 (−60) corresponding to the loss of C 2 H 4 O 2 ascribable to neutral loss of acetic acid (substituent in C‐3) or methoxy formate moiety (chain in position C‐11); m/z 513 (−100) tiglic acid C 5 H 8 O 2 (C‐1), m/z 581 (−32) corresponding to the loss of formaldehyde (substituent at C‐4).…”
Section: Resultsmentioning
confidence: 99%
“…The chemical composition of M. azedarach is highly complex and have been subject to several investigations aimed to evaluate the presence of bioactive constituents [7,11–17] . Previous article revealed that leaves contains phenylpropanoids and flavonoids like myricetin, quercetin, kaempferol and isorhamnetin derivatives [13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The areas of the leaves consumed by the silkworm were measured by using piece together method, and the antifeedant activity (%) were calculated as the following [(CÀ T)/(C + T)] × 100, while C and T presented the consumed areas in the control and tested leaves, respectively. [16] Attraction rate ¼ ½ðTÀ CÞ=ðC þ TÞ� � 100…”
Section: Antifeedant Bioassaysmentioning
confidence: 99%
“…Limonoids are widely found in leaves, bark, fruits, seeds, and kernels throughout the Meliaceae and Rutaceae. 1 This type of compound revealed various interesting biological effects such as antifeedant, 1,2 cytotoxic, 3,4 antibacterial, anti-human immunodeficiency virus, and human carboxylesterase 2 inhibitory 5 activities.…”
mentioning
confidence: 99%